Peranan Psikologi Pendidikan dalam Teknologi Pendidikan - Suharto, Dimas (Indonesian Journal of Learning and Instructional Innovation, 2023)
Education has a big responsibility in delivering the nation's next generation in facing the times. To design a good education requires an in-depth analysis of the characteristics of students. This knowledge can be obtained through the study of educational psychology. Educational psychology is basically a branch of psychology that specializes in how to understand teaching and learning in educational settings. Educational technology is a system for facilitating the course of learning activities both individually and in groups so that an effective and efficient learning and teaching process is realized, as well as a systematic and critical approach to solving problems in education and can contribute to developing the potential of students. This article uses the library research method where the data sources come from books, journals, scientific articles, and literature. In its application in the world of educational technology, educational psychology assists educational technologists in analyzing the needs of students both physically and mentally.